Hydrocarbons genesis of pre-Jurassic complex in Khanty-Mansiysk field (the zone of West Siberian plate local compression) - Yu.V. Korzhov; G.A. Lobova; V.I. Isaev; A.I. Starikov; M.Ya. Kuzina (Геофизический журнал, 2020)
This paper establishes the origin of hydrocarbons deposits in Jurassic and pre-Jurassic complexes in the territory of Khanty-Mansyisk field, which is associated with traps formed in the weathered Devonian carbonate sediments and in basement rocks, within the zone of compression (suture?) in the central part of the West Siberian platform. The study is relevant for substantiating oil deposits prospecting strategy considering material composition and basement tectonics of West Siberian plate.